Freeze Damage Symptoms and Recovery for Citrus - Mongi Zekri; W. Chris Oswalt; Steve Futch; Gary England; Camille McAvoy; Laurie Hurner; Parker Platts (EDIS)
Citrus trees are evergreen, never become fully dormant, and cannot withstand temperatures as low as those tolerated by deciduous trees. But citrus trees can become preconditioned or acclimated to cool air temperatures that occur in late fall and winter. One of the best ways to lessen cold injury and to hasten recovery from cold damage is to maintain healthy trees. This 5-page fact sheet discusses the symptoms of freeze damage and ways to help recover trees that have been damaged. Written by Mongi Zekri, Chris Oswalt, Steve Futch, Gary England, Camille McAvoy, Laurie Hurner, and Parker Platts, and published by the Horticultural Sciences Department, January 2016.